Methanol extract of Nigella sativa seed induces changes in the levels of neurotransmitter amino acids in male rat brain regions - Tarek El-Naggar; María Emilia Carretero; Carmen Arce; María Pilar Gómez-Serranillos (Taylor & Francis Group, 2017)
Context: Nigella sativa L. (Ranunculaceae) (NS) has been used for medicinal and culinary purposes. Different parts of the plant are used to treat many disorders. Objective: This study investigates the effects of NS methanol extract on brain neurotransmitter amino acid levels. Materials and methods: We measured the changes in aspartate, glutamate, glycine and γ-aminobutyric acid in five brain regions of male Wistar rats after methanol extract treatment. Animals were injected intraperitoneally with saline solution (controls) or NS methanol extract (equivalent of 2.5 g/kg body weight) and sacrificed 1 h later or after administering 1 daily dose for 8 days. The neurotransmitters were measured in the hypothalamus, cortex, striatum, hippocampus and thalamus by HPLC. Results and discussion: Results showed significant changes in amino acids compared to basal values. Glutamate increased significantly (16-36%) in the regions analyzed except the striatum. Aspartate in the hypothalamus (50 and 76%) and glycine in hippocampus (32 and 25%), thalamus (66 and 29%) and striatum (75 and 48%) also increased with the two treatment intervals. γ-Aminobutyric acid significantly increased in the hippocampus (38 and 32%) and thalamus (22 and 40%) but decreased in the cortex and hypothalamus although in striatum only after eight days of treatment (24%). Conclusion: Our results suggest that injected methanol extract modifies amino acid levels in the rat brain regions. These results could be of interest since some neurodegenerative diseases are related to amino acid level imbalances in the central nervous system, suggesting the prospect for therapeutic use of NS against these disorders.